A giant degenerative uterine leiomyoma mimicking an ovarian neoplasm: Case report - Van Trung Hoang; The Huan Hoang; Hoang Anh Thi Van; Ngoc Trinh Thi Pham; Vichit Chansomphou; Thanh Tam Thi Nguyen; Cong Thao Trinh; Duc Thanh Hoang (SAGE Open Medical Case Reports)
Uterine leiomyoma, also referred to as fibroid or myoma, is a prevalent benign tumor that can present with a range of clinical manifestations. The symptoms, which vary based on the tumor’s location, size, and number, include pain, constipation, urinary disturbances, and abnormal menstrual bleeding. Certain types of uterine leiomyomas, such as pedunculated subserosal myomas or large degenerating cystic myomas, may closely mimic ovarian tumors, leading to significant diagnostic and management challenges. In this report, we present the case of a 47-year-old woman who experienced severe dyspnea and abdominal distension. Comprehensive radiological evaluation revealed a massive lesion, with both solid and cystic components, occupying the entire abdominopelvic cavity. Histological analysis confirmed the diagnosis of cellular leiomyoma. This case underscores the importance of considering degenerative cystic myoma in the differential diagnosis of large, cystic intra-abdominal tumors of unknown origin, to avoid misdiagnosis and ensure appropriate management.